298. COMPLIANCE FOR TRIMODALITY TREATMENT OF LOCALLY ADVANCED ESOPHAGEAL CANCER: EXPERIENCE FROM A CANCER CENTRE IN NORTH-EAST INDIA. (24th September 2022) - Das, Gaurav; Sarma, Gautam; Roy, Partha
Abstract: Neoadjuvant chemoradiation (NACRT) is a standard approach for treatment of locally advanced esophageal cancer. In real-world scenario, there are several challenges to the completion of such treatment. We aim to estimate the completion rates of such treatment and also estimate the treatment response. Retrospective, observation single-institute study. Study duration was from 1st June 2018 to 30th June 2021. Data was collected from patient's records and results were presented in median values, range and percentages. A total of 82 patients were planned for trimodality treatment in the Joint Tumour Board during the study period. The number of patients who completed the NACRT was 55 (67.1%). Of them, 11 (13.4%) defaulted by not undergoing esophagectomy and 4 patients (4.9%) had inoperable disease at surgery. A total of 42 patients (51.2% of intention to treat population) actually completed the trimodality treatment. Trans-thoracic esophagectomy was done in 35 and transhiatal esophagectomy in 7 patients. Complete pathological response of both the primary and the nodes (pCR) was noted in 12 patients (26.1%). The compliance for trimodality treatment approach is a key area for improvement in esophageal cancer treatment and we need to decrease 'drop outs' due to temporary symptom relief, remoteness of residence, financial hurdles, treatment toxicity with an efficient system of care delivery.